Penggunaan Model Pembelajaran Savi Berbantuan Aplikasi Capcut dalam Meningkatkan Kemampuan Berbicara pada Materi Teks Negosiasi Siswa Kelas X di SMKN 2 Cikarang Barat - Ramadhan, Hilmi Zacky; Rosalina, Sinta; Suprihatin, Dewi (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to examine the effectiveness of the SAVI (Somatic, Auditory, Visual, Intellectual) learning model integrated with the CapCut application in improving students' speaking skills on negotiation text material in Grade X of SMKN 2 Cikarang Barat. The students faced several challenges, including difficulties in structuring and delivering arguments, improper use of body language and intonation, and low confidence when speaking publicly. This research employed a quantitative method using a Nonequivalent Control Group Design. Data were collected through pretests and post tests, supported by documentation and observation. The results indicate that the implementation of the SAVI model with CapCut significantly enhances students' speaking skills compared to conventional teaching methods. This approach not only improves linguistic competence but also fosters creativity, active engagement, and student readiness for real-world communication challenges.